Zinc-free polymerized rosin and preparation method thereof
During the preparation process of polymerized rosin, the coordinated cooperation between oxaloacetic acid and phosphotungstic acid is used to remove zinc residues, solving the problem of high zinc content, achieving high yield and high quality polymerized rosin products, suitable for high-end products Ink and other fields.
Patent Information
- Application Number
- CN202411551687.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-01
AI Technical Summary
In the existing polymeric rosin production methods, zinc chloride sulfuric acid method cannot completely remove zinc residues, resulting in high zinc content, limiting its use in high-grade ink and other applications.
During the preparation of polymerized rosin, the coordinated coordination of oxaloacetic acid and phosphotungstic acid is used to form a complex reacted with zinc ions, thereby effectively removing trace amounts of zinc.
It realizes a polymerized rosin product without zinc residue, maintains high yield, improves the dispersion and printing effect of ink, and meets the quality requirements of high-grade inks.
Smart Images

Figure CN119410271A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymerized rosin, and more specifically, to a zinc-free polymerized rosin and a preparation method thereof. Background Art
[0002] Polymerized rosin is an important chemical raw material, mainly dimer, which is a mixture of rosin and rosin hydrocarbons. This mixture does not crystallize, has a higher softening point than ordinary rosin, and shows more stable physical properties. Among them, the content of dimer is about 20%-50%. This component has high stability and is not prone to oxidation. Due to its unique chemical properties, polymerized rosin is widely used in the preparation of adhesives, inks and other products.
[0003] There are two main methods for producing polymerized rosin on the market: sulfuric acid method and zinc chloride sulfuric acid method. Although the sulfuric acid method can avoid the problem of zinc residue during the production process, its polymerization reaction yield is low, usually between 80% and 83%. This not only leads to low production efficiency, but also increases production costs; at the same time, the pure sulfuric acid method also has a high safety risk. In contrast, the zinc chloride sulfuric acid method has a higher polymerization yield, which can reach 90%, and the production efficiency is also significantly improved. However, the defect of this method is that zinc cannot be completely removed, and the zinc content can only be controlled at 35-50 mg / g. This poses a great limitation for application areas that have strict requirements on zinc content, such as ink manufacturing.
[0004] In the domestic industry standards, polymerized rosin products used in inks must meet the requirements of a softening point of 115-140°C, an acid value (acid value) of about 150 mgKOH / g, and a zinc content of no more than 32 mg / kg. However, due to the problem of zinc residue, when polymerized rosin produced by existing technology is used in high-end inks, the ink's antioxidant (anti-aging) properties are often insufficient due to excessive zinc content. As time goes by, the acidic components and residual zinc in the ink are easily oxidized by moisture, causing the printed text or color to become blurred, which cannot meet the requirements of high-end murals and other printed products that need to maintain bright colors and clarity for a long time.
[0005] Therefore, how to maintain a high product yield while completely removing zinc residues has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In order to maintain a high yield of the product and completely remove zinc residues, the present application provides a zinc-free polymerized rosin and a preparation method thereof.
[0007] In a first aspect, the present application provides a zinc-free polymerized rosin, which adopts the following technical solution: A zinc-free polymerized rosin, comprising the following raw materials: horsetail rosin, inorganic acid, zinc chloride, solvent, oxaloacetic acid, and phosphotungstic acid; The inorganic acid accounts for 0.6-1% of the mass of the mass rosin, the zinc chloride accounts for 2.5-4.5% of the mass of the mass rosin, the solvent accounts for 75-85% of the mass of the mass rosin, the oxaloacetic acid accounts for 0.04-0.08% of the mass of the mass rosin, and the phosphotungstic acid accounts for 0.04-0.08% of the mass of the mass rosin.
[0008] Preferably, the inorganic acid is 0.8-1% of the mass of mass rosin, the zinc chloride is 3-3.5% of the mass of mass rosin, the solvent is 75-80% of the mass of mass rosin, the oxaloacetic acid is 0.06-0.08% of the mass of mass rosin, and the phosphotungstic acid is 0.04-0.06% of the mass of mass rosin.
[0009] The zinc in zinc chloride is a heavy metal and will form a complex in the reaction system. However, it is difficult to completely remove trace amounts of zinc during the water washing process, which is precisely the technical problem that the current zinc chloride-sulfuric acid method cannot solve.
[0010] The entire preparation process of the present application includes three steps: polymerization, water washing (washing reaction liquid), and distillation. The purpose of the water washing step is to remove the acidity of the polymerization reaction liquid, that is, to keep the pH under neutral conditions, to obtain a clean polymerized rosin ester liquid after washing the reaction liquid, and finally to distill to obtain the product. However, paradoxically, under neutral conditions of water washing, trace amounts of zinc will dissolve in water, making it difficult to remove.
[0011] The present application can effectively solve the above technical problems by cooperating with oxaloacetic acid and phosphotungstic acid. After washing with water, oxaloacetic acid and phosphotungstic acid are added to react with trace amounts of zinc to form a complex (white precipitate, which can be filtered and removed), thereby removing trace amounts of zinc. Finally, water is washed again to remove unreacted oxaloacetic acid and phosphotungstic acid. The use of oxaloacetic acid and phosphotungstic acid can remove zinc without affecting the quality and yield of polymerized rosin.
[0012] In addition, the zinc-free polymerized rosin provided in the present application can be used specifically in the field of inks. If the oxaloacetic acid and phosphotungstic acid are not completely removed, the quality of the ink will not be affected. A small amount of oxaloacetic acid and phosphotungstic acid in the zinc-free polymerized rosin can improve the dispersibility of the ink system, making the pigment and filler more evenly dispersed, thereby effectively improving the printing effect and color saturation of the ink.
[0013] Preferably, the mass ratio of oxaloacetic acid to phosphotungstic acid is (0.8-1.2): (0.8-1.2).
[0014] By adopting the above technical solution, the mass ratio of oxaloacetic acid to phosphotungstic acid is further limited, so that oxaloacetic acid and phosphotungstic acid can more fully coordinate with zinc ions to form a stable complex. In addition, oxaloacetic acid and phosphotungstic acid can competitively coordinate with zinc ions to form a more complex acid-base balance system, thereby accelerating the removal of zinc ions.
[0015] Preferably, the inorganic acid is concentrated sulfuric acid.
[0016] Preferably, the solvent is at least a mixture of one or more of toluene, xylene, gasoline and naphtha.
[0017] Preferably, the zinc chloride is anhydrous zinc chloride.
[0018] In a second aspect, the present application provides a method for preparing zinc-free polymerized rosin, using the following technical solution: A method for preparing zinc-free polymerized rosin comprises the following steps: Step 1: Mix the solvent and horsetail rosin and heat at 50-60℃ until they are completely dissolved; Step 2: Add inorganic acid dropwise to the material of step 1 for isomerization, and the isomerization time is 1-2h; Step 3: Add zinc chloride to the material in step 2 and polymerize at 105-115° C. for 4-6 hours; Step 4: washing the supernatant of step 3 with water; Step 5: Add oxaloacetic acid and phosphotungstic acid to the material washed in step 4, mix well, and continue washing; Step 6: distill the organic phase washed with water in step 5 to remove the solvent at 235-245° C., maintain the vacuum degree at -0.085 to -0.099 MPa, and steam with active gas for 20-40 minutes to obtain zinc-free polymerized rosin.
[0019] By adopting the above technical scheme, during the water washing process, an appropriate amount of oxaloacetic acid and phosphotungstic acid are introduced, and the two react chemically with the trace zinc remaining in the system to generate an easily separable zinc complex, thereby achieving efficient removal of trace zinc.
[0020] The synergistic use of oxaloacetic acid and phosphotungstic acid can effectively remove zinc while promoting the quality and yield of polymerized rosin, and also provide new ideas and methods for technological progress in ink manufacturing and related fields.
[0021] Preferably, before mixing the solvent and the masson rosin in step 1, the masson rosin is crushed into pieces of 1-3 cm in size.
[0022] By adopting the above technical solution, the horsetail rosin is broken into small sizes so that it can be quickly and fully dissolved in the solvent, which is convenient for subsequent reactions.
[0023] In summary, this application has the following beneficial effects: 1. Traditional inks may contain trace amounts of zinc, which may trigger chemical reactions under certain conditions, causing the ink color to change or the printed surface to become blurred. The zinc-free polymerized rosin provided in this application can achieve no zinc residue, and this breakthrough effectively solves the problem of discoloration and blurring that is easy to occur when ink is applied to products.
[0024] 2. The present application not only solves the problem of no zinc residue in the product, but also maintains a high yield, which brings significant economic value to the manufacturer. The conventional zinc chloride sulfuric acid method product has a zinc content of up to 32 mg / g, while the product of the present invention does not contain zinc at all. This means that while maintaining product quality, the manufacturer can significantly reduce the waste and cost increase caused by zinc residue.
[0025] 3. This application can not only maintain a high yield of the product, but also completely remove zinc residues. The solution to this technical problem is not only a major breakthrough in the industry, but also in line with one of the key directions supported by the state. At present, the demand for high-quality polymerized rosin in domestic high-end ink and other application fields is growing, and traditional production methods are often difficult to meet these requirements. The technical solution of this application has effectively filled the gap in this field in China and provided strong support for the realization of domestic substitution. This will help break the foreign technology monopoly, enhance the overall competitiveness of the domestic ink industry, and contribute to the healthy development of the national economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a sample diagram for detecting the zinc content of the zinc-free polymerized rosin in Example 1 of the present application.
[0027] Figure 2 This is a graph showing the zinc content test results of the zinc-free polymerized rosin of Example 1 of the present application.
[0028] Figure 3 This is a sample diagram of the zinc content detection of the polymerized rosin in Comparative Example 1 of the present application.
[0029] Figure 4 This is a graph showing the zinc content test results of the polymerized rosin of Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0031] The raw materials used in the following examples and comparative examples are all commercially available products. Example
[0032] Example 1 A zinc-free polymerized rosin comprises the following raw materials: horsetail rosin, inorganic acid, zinc chloride, solvent, oxaloacetic acid and phosphotungstic acid.
[0033] The inorganic acid is 98% concentrated sulfuric acid, the zinc chloride is anhydrous zinc chloride, and the solvent is 200# gasoline.
[0034] The specific amount of each raw material is shown in Table 1.
[0035] The present application also provides a method for preparing zinc-free polymerized rosin, comprising the following steps: Step 1: Crush the horsetail rosin into 1-3cm pieces (for easier dissolution).
[0036] Step 2: Pour the crushed horsetail rosin in step 1 into the solvent quickly, stir and dissolve, and heat to 55°C for 1 hour to observe whether it is completely dissolved.
[0037] Step 3: Slowly drip concentrated sulfuric acid into the completely dissolved material in step 2 for isomerization for 1.5 hours.
[0038] Step 4: Add anhydrous zinc chloride to the isomerized material obtained in step 3, raise the temperature to 110°C for polymerization, and perform polymerization for 5 hours. After 5 hours, observe whether the acid residue in the reaction bottle is evenly distributed in the reaction bottle.
[0039] Step 5: Pour the supernatant from step 4 into a water washing kettle for water washing, add hot water that is 80% of the total amount of the material, wash and stir for 15 minutes, let it stand for 20 minutes, and drain the lower aqueous phase. Repeat the water washing.
[0040] When washing for the third time, add oxaloacetic acid and phosphotungstic acid, mix well, and continue washing according to the above method.
[0041] Wash eight times in total.
[0042] Step 6: distill the organic phase washed with water in step 5 to remove the solvent at 240° C., maintain the vacuum degree of -0.096 MPa and steam distill for 30 minutes, and then discharge the material.
[0043] The softening point of the product was determined to be 140°C, the acid value was 142 mgKOH / g, the product yield was 96.8%, and the residual zinc content was 0 mg / kg.
[0044] Specific test report reference Figure 1 , 2 .
[0045] Example 2 A zinc-free polymerized rosin, which is different from Example 1 in that the solvent is xylene.
[0046] The specific amount of each raw material is different, see Table 1 for details.
[0047] A method for preparing zinc-free polymerized rosin is different from that of Example 1 in that some parameters are different.
[0048] The specific steps include: Step 1: Crush the horsetail rosin into 1-3cm pieces (for easier dissolution).
[0049] Step 2: Pour the crushed horsetail rosin in step 1 into the solvent quickly, stir and dissolve, and heat to 50°C to dissolve for 1.5 hours, and observe whether it is completely dissolved.
[0050] Step 3: Slowly drip concentrated sulfuric acid into the completely dissolved material in step 2 for isomerization, and the isomerization lasts for 1 hour.
[0051] Step 4: Add anhydrous zinc chloride to the isomerized material obtained in step 3, raise the temperature to 105°C for polymerization, and the polymerization time is 6 hours. After 6 hours, observe whether the acid residue in the reaction bottle is evenly distributed in the reaction bottle.
[0052] Step 5: Pour the supernatant from step 4 into a water washing kettle for water washing, add hot water that is 80% of the total amount of the material, wash and stir for 15 minutes, let it stand for 20 minutes, and drain the lower aqueous phase. Repeat the water washing.
[0053] When washing for the third time, add oxaloacetic acid and phosphotungstic acid, mix well, and continue washing according to the above method.
[0054] Wash eight times in total.
[0055] Step 6: distill the organic phase washed with water in step 5 at 235°C to remove the solvent, maintain the vacuum degree at -0.085 MPa and steam distill for 40 minutes to discharge the material.
[0056] The softening point of the product was determined to be 130°C, the acid value was 146 mgKOH / g, the product yield was 93.5%, and the residual zinc content was 0 mg / kg.
[0057] Example 3 A zinc-free polymerized rosin, which is different from Example 1 in that: The solvent is toluene.
[0058] The specific amount of each raw material is different, see Table 1 for details.
[0059] A method for preparing zinc-free polymerized rosin is different from that of Example 1 in that some parameters are different.
[0060] The specific steps include: Step 1: Crush the horsetail rosin into 1-3cm pieces (for easier dissolution).
[0061] Step 2: Pour the crushed horsetail rosin in step 1 into the solvent quickly, stir and dissolve, and heat to 60°C to dissolve for 1 hour, and observe whether it is completely dissolved.
[0062] Step 3: Slowly drip concentrated sulfuric acid into the completely dissolved material in step 2 for isomerization for 2 hours.
[0063] Step 4: Add anhydrous zinc chloride to the isomerized material obtained in step 3, raise the temperature to 115°C for polymerization, and perform polymerization for 4 hours. After 4 hours, observe whether the acid residue in the reaction bottle is evenly distributed in the reaction bottle.
[0064] Step 5: Pour the supernatant from step 4 into a water washing kettle for water washing, add hot water that is 80% of the total amount of the material, wash and stir for 15 minutes, let it stand for 20 minutes, and drain the lower aqueous phase. Repeat the water washing.
[0065] When washing for the third time, add oxaloacetic acid and phosphotungstic acid, mix well, and continue washing according to the above method.
[0066] Wash eight times in total.
[0067] Step 6: distill the organic phase washed with water in step 5 at 245°C to remove the solvent, maintain the vacuum degree at -0.099 MPa and steam distill for 20 minutes to discharge the material.
[0068] The softening point of the product was determined to be 132°C, the acid value was 145 mgKOH / g, the product yield was 93.8%, and the residual zinc content was 0 mg / kg.
[0069] Example 4 A zinc-free polymerized rosin is different from Example 1 in that the specific amounts of the raw materials are different, as shown in Table 1.
[0070] The softening point of the product was determined to be 138°C, the acid value was 141 mgKOH / g, the product yield was 96.4%, and the residual zinc content was 0 mg / kg.
[0071] Table 1 raw material Example 1 Example 2 Example 3 Example 4 Horsetail rosin(g) 300 300 300 300 Inorganic acid(g) 1.8 2.4 3 1.8 Zinc chloride(g) 10.5 7.5 13.5 9 Solvent(g) 240 225 255 240 Oxaloacetate(g) 0.18 0.24 0.18 0.12 Phosphotungstic acid(g) 0.18 0.15 0.12 0.24 Comparative Example Comparative Example 1 A polymerized rosin, which is different from Example 1 in that oxaloacetic acid and phosphotungstic acid are omitted.
[0072] The product yield was determined to be 90.4% and the residual zinc content was 28 mg / kg.
[0073] Specific test report reference Figure 3 , 4 .
[0074] Comparative Example 2 A polymerized rosin, which is different from Example 1 in that oxaloacetic acid and phosphotungstic acid are replaced by oxalic acid.
[0075] The product yield was determined to be 91.1% and the residual zinc content was 10 mg / kg.
[0076] Comparative Example 3 A polymerized rosin, which is different from Example 1 in that oxaloacetic acid is replaced by phosphotungstic acid, that is, the oxaloacetic acid is 0 g and the phosphotungstic acid is 0.36 g.
[0077] The product yield was determined to be 92.6% and the residual zinc content was 5 mg / kg.
[0078] Comparative Example 4 A polymerized rosin, which is different from Example 1 in that oxaloacetic acid is replaced by phosphotungstic acid, that is, the oxaloacetic acid is 0.36 g and the phosphotungstic acid is 0.
[0079] The product yield was determined to be 92.3% and the residual zinc content was 6 mg / kg.
[0080] Performance testing Sample preparation: 30 parts of polymerized rosin of Example 1-4 and Comparative Example 1-4, 100 parts of acrylate resin, 5 parts of aqueous wax emulsion (D-816), 1 part of propylene glycol butyl ether, 200 parts of water, 0.5 parts of aqueous dispersant, 5 parts of ethanol, and 0.5 parts of pigment red. The above raw materials were put into a disperser and stirred evenly at 400 r / min to obtain a sample to be tested.
[0081] The above test samples were tested with reference to GB / T 13217.2-2024 "Test method for ink gloss", and the initial gloss was recorded in Table 2.
[0082] The tested printed samples were placed in an environment with a humidity of 95% and a temperature of 50°C for 7 days. During the placement period, they were also exposed to ultraviolet light with an intensity of 42mW / cm 2 After irradiation for 2 hours under the conditions of , the glossiness of the treated print was tested again after 7 days, and recorded as the glossiness after treatment, which is recorded in Table 2.
[0083] Table 2 Combining the performance measurements of the polymerized rosin of Examples 1-4 and Comparative Examples 1-4, it can be seen that the polymerized rosin of Examples 1-4 can all be zinc-free, while that of Comparative Examples 1-4 cannot be zinc-free and exhibits zinc residues to varying degrees.
[0084] According to the test data in Table 2, the initial glossiness of the zinc-free polymerized rosin in Examples 1-4 is higher than that in Comparative Examples 1-4, which indicates that the inks prepared by the zinc-free polymerized rosin in Examples 1-4 have better glossiness and better quality.
[0085] After the treatment, the glossiness of the zinc-free polymerized rosin of Examples 1-4 did not decrease or only decreased slightly compared with the initial glossiness, which means that since the polymerized rosin does not have residual zinc, the problem of zinc affecting the quality of the ink is avoided, thereby effectively enhancing the anti-oxidation property of the ink.
[0086] On the other hand, although the initial glossiness of the polymerized rosin of Comparative Examples 1-4 is similar to that of Examples 1-4 and only slightly lower than that of Examples 1-4, after treatment, the glossiness after treatment is significantly lower than the initial glossiness. This indicates that the polymerized rosin of Comparative Examples 1-4 cannot impart good antioxidant properties to the high-grade ink when used in the high-grade ink. As time goes by, the printing effect of the ink will be greatly reduced and cannot meet the requirements of high-grade printed products.
[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A zinc-free polymerized rosin, characterized in that: The raw materials include: horsetail rosin, inorganic acid, zinc chloride, solvent, oxaloacetic acid, phosphotungstic acid; The inorganic acid is 0.6-1% of the mass of the mass rosin, the zinc chloride is 2.5-4.5% of the mass of the mass rosin, the solvent is 75-85% of the mass of the mass rosin, the oxaloacetic acid is 0.04-0.08% of the mass of the mass rosin, and the phosphotungstic acid is 0.04-0.08% of the mass of the mass rosin.
2. The zinc-free polymerized rosin according to claim 1, characterized in that: The mass ratio of oxaloacetic acid to phosphotungstic acid is (0.8-1.2): (0.8-1.2).
3. The zinc-free polymerized rosin according to claim 1, characterized in that: The inorganic acid accounts for 0.8-1% of the mass of mass rosin, the zinc chloride accounts for 3-3.5% of the mass of mass rosin, the solvent accounts for 75-80% of the mass of mass rosin, the oxaloacetic acid accounts for 0.06-0.08% of the mass of mass rosin, and the phosphotungstic acid accounts for 0.04-0.06% of the mass of mass rosin.
4. The zinc-free polymerized rosin according to claim 1, characterized in that: The inorganic acid is concentrated sulfuric acid.
5. The zinc-free polymerized rosin according to claim 1, characterized in that: The solvent is at least a mixture of one or more of toluene, xylene, gasoline and naphtha.
6. The zinc-free polymerized rosin according to claim 1, characterized in that: The zinc chloride is anhydrous zinc chloride.
7. A method for preparing the zinc-free polymerized rosin according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Mix the solvent and horsetail rosin and heat at 50-60℃ until they are completely dissolved; Step 2: Add inorganic acid dropwise to the material of step 1 for isomerization, and the isomerization time is 1-2h; Step 3: Add zinc chloride to the material in step 2 and polymerize at 105-115° C. for 4-6 hours; Step 4: washing the supernatant of step 3 with water; Step 5: Add oxaloacetic acid and phosphotungstic acid to the material washed in step 4, mix well, and continue washing; Step 6: distill the organic phase washed with water in step 5 to remove the solvent at 235-245° C., maintain the vacuum degree at -0.085~-0.099 MPa, and steam with active gas for 20-40 minutes to obtain zinc-free polymerized rosin.
8. The method for preparing zinc-free polymerized rosin according to claim 7, characterized in that: In the step 1, before mixing the solvent and the masson rosin, the masson rosin is crushed into pieces of 1-3 cm.
Citation Information
Patent Citations
Preparation method of polymerized rosin
CN104087181A
Method for preparing polymerized rosin
CN104419323A
Producing method for high softening point polymer resin
CN1583923A
Method of polymerizing rosin
US4536333A